Dysregulated daily rhythmicity of neuronal resting-state networks in MCI patients. (November 2014) - Blautzik, Janusch; Vetter, Céline; Schneider, Annalisa; Gutyrchik, Evgeny; Reinisch, Veronika; Keeser, Daniel; Paolini, Marco; Pöppel, Ernst; Bao, Yan; Reiser, Maximilian; Roenneberg, Till; Meindl, Thomas
<x xml:space="preserve">Abstract</x> In young healthy participants, the degree of daily rhythmicity largely varies across different neuronal resting-state networks (RSNs), while it is to date unknown whether this temporal pattern of activity is conserved in healthy and pathological aging. Twelve healthy elderly (mean age = 65.1 ± 5.7 years) and 12 patients with amnestic mild cognitive impairment (aMCI; mean age = 69.6 ± 6.2 years) underwent four resting-state functional magnetic resonance imaging scans at fixed 2.5 h intervals throughout a day. Time courses of a RSN were extracted by a connectivity strength and a spatial extent approach performed individually for each participant. Highly rhythmic RSNs included a sensorimotor, a cerebellar and a visual network in healthy elderly; the least rhythmic RSNs in this group included a network associated with executive control and an orbitofrontal network. The degree of daily rhythmicity in aMCI patients was reduced and dysregulated. For healthy elderly, the findings are in accordance with results reported for young healthy participants suggesting a comparable distribution of daily rhythmicity across RSNs during healthy aging. In contrast, the reduction and dysregulation of daily rhythmicity observed in aMCI patients is presumably indicative of underlying neurodegenerative processes in this group.